Expression of the eRF1 translation termination factor is controlled by an autoregulatory circuit involving readthrough and nonsense-mediated decay in plants - Nyikó, Tünde (Nucleic Acids Res, 2017)
When a ribosome reaches a stop codon, the eukaryotic Release Factor 1 (eRF1) binds to the A site of the ribosome and terminates translation. In yeasts and plants, both over- and underexpression of eRF1 lead to altered phenotype indicating that eRF1 expression should be strictly controlled. However, regulation of eRF1 level is still poorly understood. Here we show that expression of plant eRF1 is controlled by a complex negative autoregulatory circuit, which is based on the unique features of the 3΄untranslated region (3΄UTR) of the eRF1-1 transcript. The stop codon of the eRF1-1 mRNA is in a translational readthrough promoting context, while its 3΄UTR induces nonsense-mediated decay (NMD), a translation termination coupled mRNA degradation mechanism. We demonstrate that readthrough partially protects the eRF1-1 mRNA from its 3΄UTR induced NMD, and that elevated eRF1 levels inhibit readthrough and stimulate NMD. Thus, high eRF1 level leads to reduced eRF1-1 expression, as weakened readthrough fails to protect the eRF1-1 mRNA from the more intense NMD. This eRF1 autoregulatory circuit might serve to finely balance general translation termination efficiency.